High Intensity Focused Ultrasound-Responsive and Ultrastable Cerasomal Perfluorocarbon Nanodroplets for Alleviating Tumor Multidrug Resistance and Epithelial–Mesenchymal Transition - Ma, Xiaotu; Yao, Meinan; Shi, Jiyun; Li, Xiaoda; Gao, Yu; Luo, Qi; Hou, Rui; Liang, Xiaolong; Wang, Fan (ACS nano, 2020)
Hypoxia is a hostile hallmark of most solid tumors, which often leads to multidrug resistance (MDR) and causes the failure of chemotherapy. Hypoxia also promotes epithelial–mesenchymal transition (EMT), leading to acceleration of tumor metastasis. Many chemotherapeutic drugs can further exacerbate hypoxia and thus promote metastasis. Therefore, relieving hypoxia is necessary for chemotherapy to inhibit both MDR and EMT. Herein, highly stable cerasomal perfluorocarbon nanodroplets with an atomic layer of polyorganosiloxane surface and pH-sensitive tumor-targeting peptide (D-vPCs-O2) were fabricated to co-deliver oxygen and therapeutic drug, doxorubicin. High-intensity focused ultrasound (HIFU) was utilized to trigger the co-release of doxorubicin and oxygen and simultaneously enhance ultrasound imaging, therefore achieving imaging-guided drug delivery. Mild-temperature HIFU (M-HIFU) not only triggered oxygen release from nanodroplets but also slightly elevated tumor temperature to accelerate tumor blood flow. The oxygen release and temperature elevation jointly relieved tumor hypoxia and alleviated MDR, which greatly enhanced the drug therapeutic efficacy as compared to clinically used doxorubicin and Doxil. Overall side effects were also largely reduced owing to the ultrastable drug loading of cerasome. The improvement of insufficient chemotherapy and the relief of tumor hypoxia corporately down-regulated TGF-β1, leading to the alleviation of EMT, and therefore significantly inhibited tumor metastasis. When “D-vPCs-O2 + M-HIFU” was utilized as a neoadjuvant chemotherapy, nanodroplets down-regulated heat shock proteins, reducing tumor relapse after the high-temperature HIFU (H-HIFU)-mediated hyperthermia ablation. The chemo-hyperthermia therapy totally eradicated tumors without any relapse or metastasis, providing a promising way to treat the triple-negative breast cancer, which is highly malignant, easily metastatic, and lacks effective treatments.